Comparative Study on Graph-based Information Retrieval: the Case of XML Document - Belahyane, Imane; Mammass, Mouad; Abioui, Hasna; Moutaoukkil, Assmaa; Idarrou, Ali (International Journal of Advanced Engineering, Management and Science, 2021)
The processing of massive amounts of data has become indispensable especially with the potential proliferation of big data. The volume of information available nowadays makes it difficult for the user to find relevant information in a vast collection of documents. As a result, the exploitation of vast document collections necessitates the implementation of automated technologies that enable appropriate and effective retrieval. In this paper, we will examine the state of the art of IR in XML documents. We will also discuss some works that have used graphs to represent documents in the context of IR. In the same vein, the relationships between the components of a graph are the center of our attention.